THE SYNTACTICAL ANALYSIS ON LETTER WRITTEN BY STUDENTS OF SMAN 1 KEDIRI - Muliani; Sugianto; Syamsul Hadi (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2021)
The aims of the research were to investigate the syntactical and the factors influencing the students’ syntctical problems in writing letter. This research used content analysis with descriptive qualitative approach. The source of data in this research were the 11th grade students’ letter writing. The data were collected once and analyzed using tree diagram analysis then clasified by using data sheet. The finding showed that there were seven syntactical problem that made by the students in letter writing. The first syntactical problem was in noun. from 13 students’ letters data it had 3 syntactical errors in noun. the second students’ syntactical problem in pronoun. from 13 students’ letters data it had 3 syntactical errors in pronoun. The third students’ syntactical problem in verb. from 13 students’ letter data it had 3 syntactical errors in verb. The fourth students’ syntactical problem in determiner. from 13 students’letters data it had 4 syntactical errors in determiner. the fifth students’ syntactical problem in preposition. from 13 students’ letters data it had 14 syntactical error in preposition. the sixth students’ problem in adjective. from 13 students’ letter data it had one syntactical error in adjective. the seventh students’ problem in tenses marker. from 13 students’ letter data it had 4 syntactical errors in tenses marker. Meanwhile, the factors that influence students’ syntactical errors were mother tongue interfernce which included in interlingual error. the data of questionnaires showed that the percentage score of interlingual error was 65% meanwhile intralingual error was 56%.